Seismic reflectivity of a carbon dioxide flux - Gómez, Julián Luis (2012)
In the context of the geological storage of carbon dioxide (CO2), thecharacterization of the injected CO2 in a reservoir is of primeimportance for volume capacity evaluation and long-term siteperformance. In this article, we aim to characterize a CO2 accumulationin a deep layered aquifer by means of its seismic reflectivity. Formodeling the vertical distribution of CO2 saturation in the reservoir,we solve the Buckley-Leverett equation with discontinuous flux function,which describes two-phase flow in porous stratified media. To solve thisequation numerically we employ a finite-difference relaxation scheme.The scheme entails an upwinding reconstruction for the spatialderivatives and an implicit-explicit Runge-Kutta scheme for timeintegrations. Once the vertical distribution of CO2 is obtained, we usea matrix propagator algorithm to compute in the frequency domain, thegeneralized reflectivity of the reservoir due to the injected gas. Thebehavior of this reflectivity controls the amplitude of seismic wavereflections and strongly conditions the detectability of the CO2 volumein the space-time domain. The numerical approach used in this article iseasy to implement and allows to quantify the reflectivity of the carbondioxide distribution in a practical way. We show that the frequencybehavior of the reservoir reflectivity may help to interpret thevertical accumulation of CO2, which can be useful as a basis fortime-lapse geophysical monitoring.